Morphogens and growth factor signalling in the myeloma bone-lining niche - Morris, EV; Edwards, CM (Springer, 2021)
Multiple myeloma is a malignancy caused by the clonal expansion of abnormal plasma cells. Myeloma cells have proven to be incredibly successful at manipulating their microenvironment to promote growth and to evade modern therapies. They have evolved to utilise the integral signalling pathways of the bone and bone marrow to drive disease progression. The bone marrow is often described in the context of a single structure that fills the bone cavity and supports normal haematopoiesis. However, within that structure exists two anatomically different niches, the perivascular niche and the endosteal niche. These contain different cell types functioning to support normal immune and blood cell production as well as healthy bone. These cells secrete numerous signalling molecules that can influence myeloma cell biology and behaviour. The endosteal niche is home to specific bone cell lineages and plays a pivotal role in myeloma cell establishment and survival. This review will concentrate on some of the signalling pathways that are hijacked by myeloma cells to shape a favourable environment, and the different influences myeloma cells are exposed to depending on their spatial location within the bone marrow.